Pengaruh Kepemilikan Manajerial dan Kepemilikan Institusional terhadap Nilai Perusahaan melalui Kinerja Keuangan pada Perusahaan Indeks LQ45 Pasca Pandemi COVID-19 - Raraz Asghari Giffarina; Azwardi Azwardi; Muizzudin Muizzudin (Owner : Riset dan Jurnal Akuntansi, 2026)
This study aims to analyze the effect of managerial ownership and institutional ownership on company value with profitability as an intervening variable in LQ45 index companies listed on the Indonesia Stock Exchange for the period 2021–2023. The study uses a quantitative approach with purposive sampling techniques on 25 companies, resulting in 75 observations. Data analysis was conducted through path analysis and Sobel's test to examine the mediating role of profitability. The results show that managerial ownership and institutional ownership have a significant positive effect on profitability and company value. Profitability was also found to have a positive effect on company value and was able to mediate the relationship between ownership structure and company value. These findings indicate that increased ownership by management and institutions can strengthen oversight mechanisms, improve management efficiency, and encourage an increase in company value. This study provides practical implications for management and investors in designing an optimal ownership structure as part of the implementation of Good Corporate Governance. In addition, the results of this study are expected to serve as a reference for capital market regulators in formulating policies that support corporate transparency and accountability, as well as enriching the academic literature related to the relationship between corporate governance, financial performance, and company value.